Design of High Input Impedance Voltage-mode Multifunction Biquad Filter with Independent Control of Natural Frequency and Quality Factor - Jardrit, Peerapat; Jaikla, Winai; Siripogdee, Surapong; Chaichana, Amornchai; Sotner, Roman; Khateb, Fabian (My University, 2020)
The voltage differencing differential input buffered amplifier (VD-DIBA) is interesting active building block for voltage-mode (VM) circuit design due to its advantage features such as electronic tuning, high impedance at input voltage ports and low impedance at output voltage port etc. In this paper, the realization of two-inputs three-outputs voltage-mode filter using VD-DIBAs is presented in this paper. The filter employs two VD-DIBAs, two resistors and two capacitors connected to ground. Four filtering responses, band-pass (BP) VM function, highpass (HP) VM function, low-pass (LP) VM function, and band-reject (BR) VM function are obtained. Two input nodes for applying input voltage signal are high impedance. The presented biquad filter employs two active devices but the quality factor (Q) is tuned without disturbing the natural frequency (ω0). Also, the natural frequency tuning is linearly and electronically done through bias current. The proposed filter is designed and simulated using VD-DIBA constructed from commercially available ICs, LM3700 and AD830. The Pspice simulation results justify the good functionality of the filtering performance.
Keywords: AD830; electronic tune; LM13700; universal filter; VD-DIBA